Design and analysis of electrical testing probe for semiconductor integrated circuit - Wong, Michael Loke Peng (2016)
In the field of Test and Measurement in Semiconductor industry, where measuring small resistances are necessary on Semiconductor IC (Integrated Circuit). Nowadays given the fact that electronics gadgets are evaluated become more advanced, the size of the gadgets is getting smaller and smaller, and getting cheaper in terms of price, this is a result of human kind is evaluating to advancement of electronics world. In this project, testing robe for Semiconductor IC was design to equip with self-sustaining scrubbing function, sustainable contact force and higher life span by Computer Aided Design (CAD). Then the most appropriate Testing Probe was selected by Analytical Hierarchy Process (AHP), which the pair-wise comparison matrix is constructed with the goal of Scrubbing function (SF), Contact force (CF), Low resistivity (LR), High current (HC), and Life span (LS). To analyze the designed Testing Probe for Semiconductor IC which fulfill the criteria, the test probe was undergo Finite Element Analysis (FEA) to determine the optimum Fatigue stress, Yield strength, maximum stress and displacement. Then the test probe was simulated under testing condition, data such as contact resistance CRES and displacement of test probe was collected until it reach its maximum life spend of 1.3 million touchdown. As result the most appropriate test probe was selected, which fulfilled all of the requirements.